From Commons to Reserves: Colonial Forestry, Agrarian Change, and Political Ecology in the Shimla Hill States, 1860–1947 - Sharma, Lekh Raj (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This paper reconstructs the environmental and political economy of the Shimla Hill States under British paramountcy, arguing that “scientific forestry,” revenue rationalization, and infrastructural integration transformed a landscape of commons into a landscape of reserves and permits. From the 1860s to the 1940s, working plans, demarcation, and lease arrangements converted customary rights of grazing, lopping, fuelwood, and timber into state-regulated privileges, monetizing access while elevating forest revenues as fiscal anchors of princely rule. These changes, paired with road-building and the Kalka–Shimla rail link, knit the hills to imperial markets, amplified extraction, and reconfigured agrarian livelihoods. Although horticulture—iconically the apple economy initiated in Kotgarh—promised a new equilibrium, it depended on the same infrastructures and rules that marginalized many smallholders. The social effects were uneven: rural stratification sharpened; women’s labor in forest collection became more precarious; and transhumant herders encountered criminalization. Yet these material pressures also fostered political mobilization. Praja Mandals in Sirmour, Bushahr, and other states linked forest restrictions and begar to civil liberties, forging a political ecology that helped steer integration into democratic India after 1947. Drawing on environmental and legal history (Guha; Sivaramakrishnan; Rangarajan), on studies of princely governance (Ramusack; Copland), and on Himalayan agrarian ecologies (Chetan Singh), the paper argues that indirect rule at altitude made forests legible to the state and, paradoxically, made the state legible to its subjects.